THE ROLE OF THE REGIONAL INSPECTORATE IN THE DECISION ON VILLAGE FUND RETURN IN POLEWALI MANDAR - Nisma Ariskha Masdar; Haliah; Nirwana; Andi Kusumawati (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
The study aims to identify the Role of the Regional Inspectorate in the Refund of Village Funds, the causes of the return of Village Funds by a number of Villages, and the obstacles faced by the Inspectorate in conducting inspections in Villages. The research method used in this article is a qualitative descriptive method. The type of data used in this study is primary data including information obtained directly from interviews with informants, while secondary data includes information taken from documents, reports, or regulations that already exist. The research informants in this study include the Inspector at the Polewali Mandar Inspectorate, the Inspector's Secretary, the Middle Expert Auditor, the Supervision Report Analyst, and the Staff. The results of the study show that the Inspectorate plays a very important role in the decisions of Village officials in returning Village Funds. With the inspection carried out by the Auditor Team from the Regional Inspectorate, a number of Village Heads decided to return Village Funds with a nominal value ranging from IDR 700,000 to IDR 27,000,000, even a number of Villages suddenly repaired roads and other infrastructure due to the impact of the return of the Village Funds. However, the Audit Team from the Inspectorate experienced internal and external obstacles in conducting the inspection. Internal obstacles consisted of limited Human Resources and the Honorarium given to the Audit Team was only Rp160,000 for transportation and accommodation costs.